OPTIMIZATION AND EVALUATION OF CLARITHROMYCIN FLOATING TABLETS USING EXPERIMENTAL MIXTURE DESIGN - (:unkn) unknown (POLSKIE TOWARZYSTWO FARMACEUTYCZNE, 2014)
The purpose of the study was to prepare and evaluate clarithromycin (CLA) floating tablets using experimental mixture design for treatment of Helicobacter pylori provided by prolonged gastric residence time and controlled plasma level. Ten different formulations were generated based on different molecular weight of hypromellose (HPMC K100, K4M, K15M) by using simplex lattice design (a sub-class of mixture design) with Minitab 16 (R) software. Sodium bicarbonate and anhydrous citric acid were used as gas generating agents. Tablets were prepared by wet granulation technique. All of the process variables were fixed. Results of cumulative drug release at 8th h (CDR 8th) were statistically analyzed to get optimized formulation (OF). Optimized formulation, which gave floating lag time lower than 15 s and total floating time more than 10 h, was analyzed and compared with target for CDR 8th (80%). A good agreement was shown between predicted and actual values of CDR 8 S with a variation lower than 1%. The activity of clarithromycin contained optimized formula against H. pylori were quantified using well diffusion agar assay. Diameters of inhibition zones vs. log10 clarithromycin concentrations were plotted in order to obtain a standard curve and clarithromycin activity.
Keywords: clarithromycin; floating tablets; modified release; experimental mixture design; H. pylori; DRUG-RELEASE; SYSTEM